Collaborative Governance in the Enforcement of Illegal Parking (A Study on the Enforcement of Illegal Fees at Minimarkets in Surabaya City) - Diaz Dwi Apriansyah; Deby Febriyan Eprilianto; Muhammad Farid Ma’ruf; Revienda Anita Fitrie (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study was motivated by the continued occurrence of illegal parking and illegal fees at minimarkets in Surabaya prior to enforcement efforts by the Surabaya City Government. These conditions indicate that parking management and coordination among the parties involved have not been functioning optimally. This study aims to analyze Collaborative Governance in the enforcement against illegal parking and illegal fees at minimarkets in Surabaya. This study employs a qualitative descriptive method, utilizing data collection techniques such as interviews, observations, documentation, and literature review. The analysis is conducted using Ansell and Gash’s (2008) Collaborative Governance theory. The findings reveal that the initial phase of parking enforcement still faces various challenges, including illegal parking fees, inadequate supervision, and inconsistent implementation of parking regulations on the ground. Facilitative leadership and institutional design have been implemented through coordination and task distribution among agencies, but still require strengthening in the implementation of sustainable cooperation. In the collaboration process, face-to-face dialogue, trust-building, commitment to the process, and shared understanding have been established through surprise inspections and direct communication in the field. Additionally, preliminary results indicate initial changes, such as the use of official uniforms by parking attendants and adjustments to parking operations at minimarkets. However, the ongoing collaboration still requires strengthening to ensure it proceeds more consistently and sustainably.